Short Communication: The species diversity and composition of roadside trees in five cities in Sumatra, Indonesia - WIRYONO WIRYONO; YANSEN YANSEN; ADITYA ADITYA; DAVID JUARA LAMHOT; JURIAH HUTAHAEAN (Society for Indonesian Biodiversity, 2018)
Wiryono, Yansen, Aditya, Lamhot DJ, Hutahaean J. 2018. Short Communication: The species diversity and composition of roadside trees in five cities in Sumatra, Indonesia. Biodiversitas 19: 1615-1621. Roadside trees make living in a city more enjoyable due to their aesthetic values and ecosystem services. The ecological benefits of roadside trees may be enhanced by increasing the species diversity and the proportion of native species. The objective of this study was to know the species diversity and composition of roadside trees in the cities of Palembang, Bengkulu, Curup, Pematang Siantar and Argamakmur, in Sumatra Island, Indonesia, varying in size and altitude. Data of trees were collected from selected streets and analyzed to determine the species richness (S), Shannon-Wiener index of diversity (H?) and Ellenberg index of community similarity (ISE). The results showed that the species richness in a city ranged from 7 to 26, with the diversity index between 1.05 and 2.08. The large and medium cities had higher S and H?. More introduced species were found, both in number of species and number of individuals, than the native ones. The similarity among cities in species composition ranged from 47 to 82%. Overall, Swietenia macrophylla, an introduced species, was the most abundant species. The S and H? values of all cities were considered low and the composition of tree species did not support the conservation of native species. It is, therefore, essential to increase the species diversity of street trees, especially by planting native species.